Effects of Surface Finishing Techniques on Properties of NiTi Coil Spring Actuators - Premwattananarakul, Natakorn; Srirussamee, Kasama; Tunthawiroon, Phacharaphon; Kumnorkaew, Theerawat; Phukaoluan, Aphinan (My University, 2025)
This research aims to investigate the effects of surface finishing techniques on phase transformation, topography, and recovery force of NiTi coil springs designed for actuator applications. The NiTi wire, with a diameter of 1 mm, was fabricated into a helical spring with an index of 9 and 20 active coils. The spring was subsequently annealed at 550 °C for 30 min and then quenched in water. The surface finishing techniques applied to the NiTi springs included chemical etching, mechanical polishing, and sand blasting. It was observed that mechanical polishing had a strong impact on topography than both chemical etching and sand blasting. After mechanical polishing, the topography of NiTi coil springs slightly changed compared to the annealed spring. The examined surface was smooth and glistening, with a surface roughness Ra of 0.175 ± 0.006 µm, nearly identical to that of the annealed spring Ra of 0.116 ± 0.021 µm. Chemical etching produced a surface oxide, yet the surface became rough due to an uncontrollable chemical reaction, i.e., the Ra value obtained from chemical etched surface (1.177 ± 0.156 µm) was higher than that of the mechanically polished spring. Meanwhile, sand blasting provided a blue-shaded surface corresponding to an excessive Ra of 1.952 ± 0.204 µm. The DSC results revealed two peaks of R-phase and martensite transformation in the cooling curve, with only austenite transformation appearing on the heating curve. According to the DSC curve, all surface finishing techniques can reduce the latent heat and affect the associated phase transformations. Consequently, the recovery force of the spring was increased by 2–5 times the initial length. The maximum stiffness (k) of 0.129 N/mm and recovery force for the surface-finished springs were provided by mechanical polishing, while the minimum values of 0.104 N/mm were yielded by sand blasting. All experimental findings offer a framework for the development of actuator springs enhanced through each surface finishing technique.
Keywords: NiTi coil spring; Phase transformation; Recovery force; Surface finishing technique; Surface roughness; Topography